Kahoot: Let’s Have Fun in English Class with It! - Pricillia Sitompul; Siswana Siswana (Syntax Corporation Indonesia, 2023)
Motivation is required to have satisfying learning echievement in English because it drives students to study seriously without being forced. To improve students’ learning motivation, English teachers can integrate the use of technology in their teaching. One of applications which is considered to improve students’ leaning motivation is Kahoot, a game-based application. This research aimed to investigate learning motivation of students of SMA N 1 Belitang after experiencing Kahoot in learning English and English teacher’s perception toward the use of Kahoot. Questionnaire was administered to 43 second grade students and interview was done with one English teacher who used it in English class. It turned out that almost all students gave positive responses on the questionnaire and after being analyzed, students’ learning motivation was categorized into high category. Moreover, the English teacher claimed that students showed more interest in English after being introduced to Kahoot and their English scores were improved. The students’ improvement in motivation and achievement were resulted from competitive atmosphere on games and interesting display on Kahoot so that they argued that learning English is a fun activity.